Proprotein convertase subtilisin/kexin type 9 and apelin in fibromyalgia syndrome - Nevsun Pihtili Taş; Rabia Aydogan Baykara; Ayhan Kamanli; Ali Gürbüz; Erkan Cure; Medine Cumhur Cüre; Mehmet Erdem; Tugce Tasar Yildirim (Archives of Rheumatology, 2024)
Objectives: This study aimed to investigate the potential roles of proprotein convertase subtilisin/ kexin type 9 (PCSK9) and apelin in the etiology of fibromyalgia syndrome (FS). Patients and methods: The retrospective study was conducted between May 2022 and February 2023. Fifty-eight female FS patients (mean age: 45.2±9.9 years; range, 25 to 66 years) and 30 age- and body mass index-matched control subjects (mean age: 43.1±9.9 years; range, 26 to 67 years) were included in the study. Apelin and PCSK9 levels of all individuals were measured using appropriate methods. Results: The levels of PCSK9 (173.2±62.2 vs. 75.1±44.1, p<0.001) and apelin (354.6±195.5 vs. 229.0±83.2, p<0.001) were significantly higher in patients with FS compared to the control group. A positive correlation was found between PCSK9 and apelin levels and various measures, including the Fibromyalgia Impact Questionnaire (FIQ), Symptom Severity Scale (SSS), Pittsburgh Sleep Quality Index (PSQI), and Beck Depression Inventory (BDI). Additionally, there was a positive correlation between apelin levels and FIQ, SSS, PSQI, Beck Anxiety Inventory, and BDI scores. The optimal cutoff value for PCSK9 in predicting FS was 110.0 ng/mL, with a sensitivity of 84.5% and specificity of 83.9% (area under the curve [AUC]=0.920, 95% confidence interval [CI]: 0.852-0.987, p<0.001). For apelin, the optimal cutoff value for predicting FS was 258.8 ng/L, with a sensitivity of 63.8% and specificity of 64.5% (AUC=0.732, 95% CI: 0.623–0.840, p<0.001). Conclusion: Our findings suggest that PCSK9 may play a role in FS etiology and potentially contribute to oxidative stress. Increased apelin levels may be a compensatory response to high oxidative stress, possibly leading to hyperalgesia. Both PCSK9 and apelin can be predictive markers for FS.